Advanced research methods in hospitality and tourism - Okumus, Fevzi; Rasoolimanesh, S. Mostafa; Jahani, Shiva (Emerald Publishing Limited, 2022)
Rapid growth in the tourism and hospitality industry highlights the importance of applied and pure research to address the theoretical and practical problems and gaps facing the industry daily, from a multitude of perspectives - the economic, social, cultural, environmental, political, and technological. Advanced Research Methods in Hospitality and Tourism reviews traditional research methods, revising them to suit the contemporary problems and research agendas. Developing recent research strategies under the umbrella of quantitative and qualitative research methods - such as the mixed-methods designs, analysing archival materials, online databases, text mining, and scientific qualitative analysis of social media historical data- can offer promising solutions. In the era of technology and big data, advanced and innovative research methods and conducting effective research to solve emerging problems in tourism and hospitality is critical, making Advanced Research Methods in Hospitality and Tourism a necessity for academics and practitioners.